O-16 The patient experience of the advance care planning process in auckland, New Zealand. (1st September 2015) - Young, Marie; Goodman, M; Telfer, B; Garrett, T
Abstract : Background: Few researchers have explored how patients experience the process of completing an Advance Care Plan (ACP) nor determined what value participants place on being involved. In 2009 one of the main healthcare providers in Auckland began a pilot programme introducing ACP to specific groups of patients. Aim: To determine if involvement in the ACP process has been of value to participants and gain participants experience on what  worked well and what could be improved. Further aims involved how different cultures experience ACP. Methods: Thirteen participants representing the diverse cultural mix of South Auckland were interviewed within a year after completing an ACP. Interviews were transcribed and key themes coded using a general inductive approach. Results: Participant experiences fell across three broad themes that centred on the ACP process, issues specific to the plan itself and issues specific to the participant. Subthemes included competency to complete, process for updating plans, meaningfulness of treatment choices listed, peace of mind for family and cultural considerations with Maaori and Pacific peoples. All participants valued their involvement in ACP. Discussion: This study demonstrated that successful implementation of an ACP programme must centre on the process of ACP and patient specific variables just as much as the content of the plan itself. Participants valued their involvement in ACP and the results highlight how the process of ACP and cultural considerations can be improved ensuring future ACP plan delivery is successful and valued by those involved. Conclusion: The findings from this study will be useful in guiding how ACP is offered to the wider community.